Essays in the demand for energy in Finnish manufacturing - Törmä, Hannu (1987)
The research has two main themes: 1) measurement of factor substitution and 2) partial and general equilibrium calculations of energy usage based on these measures. The study contains empirical applications of modern production economics and seeks to provide new and interesting information with emphasis on energy economic topics. Special attention has been given to the ways of measurement and analysis of the substitution possibilities between the energy and the non-energy factors, to the possibility of structural change in energy vs. non-energy factor substitution and to the possible differences in the ability to factor substitution between the three Nordic countries. Factor substitution has been measured through the dual cost function of the industry, which has been specified both for static and dynamic cost minimization. Demand models for the capital, labour, energy and materials factors, derived from the cost minimizing problem, have been estimated using sophisticated estimation methods, like the iterative Zellner efficient method and the ridge method. In addition to the applications with the flexible functional forms we have employed in a general equilibrium model an assumption of CES production and consumption economy. The relations of factor demands and their prices have been presented in form of the own price, cross price and substitution elasticities. Factor substitution estimates have been used in the partial and general equilibrium calculations performed. The former is represented by a calculation where we try to estimate the factor demand substitution and output effects of an assumed negative energy crises. The general equilibrium approach is illustrated by a calculation where we try to measure the allocational and welfare effects of the recent Finnish energy tax reform. The estimated static and dynamic systems of factor demand equations tend to give a differing picture of the factor substitution possibilities. The common result is however, that substitution dominates complementarity in factor relations and that the demand for factors is inelastic with respect to the changes in their own price. The general equilibrium energy tax: reform simulations revealed that the partial value added type energy tax: reform causes small welfare losses to the representative consumer.